2016
DOI: 10.1111/afe.12197
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of habitat use by the Asian citrus psyllid,Diaphorina citri, as influenced by abiotic and biotic growing conditions

Abstract: 1 The Asian citrus psyllid Diaphorina citri Kuwayama (Hemiptera: Liviidae) is an economically important pest of citrus throughout Asia and the Americas because it transmits Candidatus Liberibacter asiaticus (CLas), which is the presumed causal agent of citrus greening disease. 2 We investigated whether biotic and abiotic characteristics can be used to predict Diaphorina citri population abundance and assessed whether agricultural intensity explained the distribution of D. citri populations during winter dorman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…In this period, 65% of the total psyllids were collected on sticky traps. Studies with small spatial time series (2 years and 2–3 sampling points), and with a resident population of psyllids (areas with poor or no control), showed that population peaks occur during spring and summer in SPS (Yamamoto et al., 2001) and Florida, USA (Hall et al., 2008; Lewis‐Rosenblum et al., 2015; Pelz‐Stelinski et al., 2016). The same was observed by Hernández‐Landa (2018) and Hall and Hentz (2011), who observed peaks of D. citri population occurring in the summer and spring, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In this period, 65% of the total psyllids were collected on sticky traps. Studies with small spatial time series (2 years and 2–3 sampling points), and with a resident population of psyllids (areas with poor or no control), showed that population peaks occur during spring and summer in SPS (Yamamoto et al., 2001) and Florida, USA (Hall et al., 2008; Lewis‐Rosenblum et al., 2015; Pelz‐Stelinski et al., 2016). The same was observed by Hernández‐Landa (2018) and Hall and Hentz (2011), who observed peaks of D. citri population occurring in the summer and spring, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Populations of adult D. citri peaked during May, Jun, and Jul in conventional groves, while similar peaks were not observed in organic counterparts. Another factor explain-ing higher psyllid populations in intermittently sprayed than organic groves observed here might be that the level of insecticide input used was insufficient to adequately reduce D. citri populations as similarly observed in Pelz-Stelinski et al (2017), yet sufficient to disrupt normal activity of natural enemies. More D. citri found in intermittently managed conventional groves also could indicate some level of insecticide resistance among populations of D. citri in these groves.…”
Section: Discussionmentioning
confidence: 65%
“…The vector, D. citri, was identified in Florida in 1998 (Zhang et al 2014;Alvarez et al 2016). Recommended management practices for huanglongbing include use of disease free stock, inoculum removal by destruction of infected trees, and suppression of D. citri populations with insecticides (Brlansky et al 2009;Alvarez et al 2016;Pelz-Stelinski et al 2017). To date, there is no cure for the disease.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations